Population prevalence of Down's syndrome in the United Kingdom. Issue 9 (28th March 2016) - Alexander, M.; Ding, Y.; Foskett, N.; Petri, H.; Wandel, C.; Khwaja, O.
Abstract: Background: Aim was to estimate the age and sex‐stratified prevalence of Down's syndrome (DS) in the United Kingdom (UK) general population using a large primary care database. Method: Data source was the Clinical Practice Research Datalink. We divided the number of individuals with a record of DS present on 01/07/2014 by the total number of individuals, and computed Wilson's confidence intervals. Prevalence by age and sex was represented using local linear smoothing plots. Results: On July 1 st 2014, 1159 females and 1317 males with DS were present in the data, corresponding to a prevalence of 5.9 per 10 000 (95% CI: 5.5; 6.2) in females and 6.8 (6.5; 7.2) per 10 000 in males. Prevalence of DS was increased in individuals aged 40 to 55 years compared to adjacent age groups. Conclusions: A relative peak prevalence of DS at age 40–55 years may be attributed to the combined effects of a rise in life expectancy and the still limited availability of selective abortion.